Penerapan Kewajiban Advokat dalam Undang-Undang Nomor 18 Tahun 2003 terhadap Keabsahan Proses Pemeriksaan Tersangka dalam Penyidikan - Andhea Frastika; Anjar Rusadi; Stevri Iskandar (GLOBAL SCIENTS PUBLISHER, 2025)
This article analyzes the implementation of advocate obligations under Law Number 18 of 2003 and its impact on the validity of the suspect examination process during the investigation stage. This normative legal research reveals that the obligation of advocate accompaniment is a crucial element of the principles of due process of law and fair trial. The effective presence of an advocate functions as a control against the potential abuse of power by investigators and ensures the fulfillment of the suspect's constitutional rights. Conversely, the ineffectiveness of the advocate's role such as merely formalistic accompaniment directly impacts the weakening of the suspect's rights protection, the fragility of the evidence construction, and potentially creates legal defects in the Investigation Report (BAP). This article concludes that the optimal enforcement of advocate obligations is an absolute prerequisite for realizing a valid, fair, and integral investigation process.